Non-invasive treatment in pain therapy with the iontophoretic technique - Paolo Desio (Publiediting, 2006)
From January 2001 to December 2003, 52 patients, 31 females and 21 males, aged between 19 and 78 years, underwent iontophoresis; they all had acute lumbar ischialgia or hiparthrosis; each cycle consisted of 4 consecutive applications in successive days. The 88% of patients (n = 46) had a positive outcome; in 12% (n = 6), pain with characteristics similar to that before treatment arouse again. No patient showed a worsening or side effects on long term. The validity and the advantages of the technique indicate that the iontophoresis is a useful non-invasive and non-traumatic therapeutic presidium, which allows direct drug use in painful area.